Making Promises in the TV Series Gilmore Girls - Suci Anggraini; Tofan Dwi Hardjanto (Universitas Gadjah Mada, 2021)
This study investigates the speech act of promising found in the first five episodes of the TV series Gilmore Girls (2000). It categorizes utterances containing promises based on the directness strategies. The direct promising strategy is identified using the IFID of the speech act of promising, that is the performative verb promise, while the indirect promising strategy is identified and categorized into 10 types of indirect promising strategy proposed by Ariff and Mugableh (2013): pure promise, discourse conditional, tautological-like expression, body-part expression, self-aggrandizing expression, time expression, courtesy-like expression, swearing expression, adjacency pair, and false promise. The results show that the most commonly used strategy was the indirect promising strategy (94.3%) as the characters in the series tend to make promises casually by not using the performative verb promise. Then, pure promise strategy is the most frequently used type of indirect promising strategy (31.3%). In addition, there are two distinctive types of indirect promising strategies found in the TV series, i.e., hidden promise and sarcastic promise strategies. This finding suggests that there are many other ways to make promises besides using the performative verb, promise and the modal verb will since the context of the conversations sometimes indicates future acts that a speaker commits to doing.